Pengaruh terpaan budaya anime terhadap keputusan berwisata wisatawan indonesia ke jepang - Wirawan, Putu Eka; Semara, I Made Trisna; Pertiwi, Putu Ratih (Jurnal Kepariwisataan dan Hospitalitas, 2025)
The number of Indonesian tourists visiting Japan has been increasing every year. According to data from JNTO Statistics, Indonesian tourists are among the groups that frequently choose Japan as their travel destination. However, Japan is not the only country in Asia that offers prominent tourist attractions. One of the factors influencing Indonesian tourists' decision to visit Japan is the strong exposure to anime culture. This study aims to analyze the extent to which anime culture influences Indonesian tourists' decision to choose Japan as a travel destination. The approach used in this study is a quantitative method with data collection techniques through closed-ended questionnaires. The data obtained were analyzed using descriptive quantitative techniques with the help of Smart PLS software.